Aktivitas Antibakteri Kombinasi Ekstrak Etanol Kulit Jeruk Manis (Citrus sinensis) Dan Daun Pepaya (Carica papaya L.) Terhadap Bakteri Salmonella typhi Penyebab Tipes - Nadela Wahyu Wijaya; Muhammad Nurul Fadel; Fahrudin Arif (Riviera Publishing, 2025)
Salmonella typhi, sweet orange peel, papaya leaves, antibacterial activity, MIC-MICD. AbstractThe background of this study is based on the high incidence of typhoid fever caused by Salmonella typhi bacteria in Indonesia and the increasing resistance of bacteria to conventional antibiotics. Therefore, alternative natural treatments are needed, such as a combination of sweet orange peel extract (Citrus sinensis) and papaya leaves (Carica papaya L.), which are known to contain antibacterial compounds. The objective of this study was to test the antibacterial activity of the ethanol extract combination of the two plants against Salmonella typhi, determine the optimal concentration, and measure the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The research methods included ethanol extraction, phytochemical testing, disk diffusion testing, and dilution testing. The results showed that the 75%:25% extract combination produced the largest inhibition zone (26.43 mm) with a very strong category, while the MIC and MBC were 6.25% and 25%, respectively. Statistical analysis confirmed significant differences between concentrations. The implications of this study are the potential of the extract combination as a safe and environmentally friendly alternative treatment for typhoid fever, as well as promoting the utilization of local natural resources.